Evaluation of Erythroid Disturbance and Thiol-Disulphide Homeostasis in Patients with Psoriasis. (5th June 2018) - Demir Pektas, Suzan; Pektas, Gokhan; Tosun, Kursad; Dogan, Gursoy; Neselioglu, Salim; Erel, Ozcan
Abstract : This study aims to assess how mean corpuscular volume (MCV), red cell distribution width (RDW), and thiol-disulphide homeostasis are altered in psoriasis patients. This is a cross-sectional review of 76 healthy volunteers and 87 psoriasis patients who were consecutively admitted to the department of dermatology. Psoriasis patients and healthy controls were statistically similar with respect to age, sex, body mass index, blood pressures, and disease duration (p > 0.05 for all). When compared to healthy controls, psoriasis patients had significantly higher MCV, RDW, C-reactive protein (CRP), disulphide, disulphide/native thiol, and disulphide/total thiol (p < 0.001 for all). However, psoriasis patients had significantly lower native thiol and native thiol/total thiol (p = 0.009 andp < 0.001, respectively). When compared to healthy controls, the patients with Psoriasis Area Severity Index (PASI) ≤ 10 and patients with PASI > 10 had significantly higher MCV, disulphide, disulphide/native thiol, and disulphide/total thiol (p < 0.001 for all). The patients with PASI ≤ 10 and patients with PASI > 10 had significantly lower native thiol/native thiol than healthy controls (p < 0.001 for all). The psoriasis patients with PASI > 10 had significantly higher RDW and CRP than healthy controls and patients with PASI ≤ 10 (p < 0.001 for all). Disulphide, disulphide/native thiol, disulphide/total thiol, and native thiol/total thiol correlate significantly with both PASI scores and disease duration. Thiol-disulphide homeostasis is enhanced in psoriasis patients. Ongoing inflammation and increased oxidative stress in psoriasis patients also trigger the formation of prooxidants which are neutralized by antioxidants such as thiols. That is why plasma thiol levels are decreased in psoriasis patients.